تقييم كفاءة بعض محطات معالجة مياه الصرف الصحي في محافظة اللاذقية - عادل عوض; حسام صبوح; مرام سعيد (Tishreen University, 2014)
على الرغم من الازدياد الكبير في عدد محطات معالجة مياه الصرف الصحي المنفذة في سورية إلاً أننا مازلنا نعاني من مشاكل عديدة ناجمة عن قلة الكفاءة في تشغيل المشاريع الحالية. يهدف هذا البحث إلى تقييم كفاءة المعالجة وجودة التدفق النهائي بما يتوافق مع المعايير التصميمية المطلوبة لأربع محطات معالجة صغيرة  في محافظة اللاذقية تعمل جميعها بتقنية التهوية المديدة. فأجريت تحاليل مخبرية وقياسات دورية لمدة ثمانية أشهر ابتداءً من شهر شباط ولغاية شهر أيلول من عام 2013 لمؤشرات: الأوكسجين المنحل (DO), والاحتياج البيوكيميائي للأوكسجين (BOD), والمواد الصلبة العالقة الكلية (TSS), والنترات (NO3-), والفوسفات (PO4-3). أظهرت النتائج أن كفاءة المعالجة كانت جيدة في محطة واحدة فقط، والتدفق النهائي حقق جميع المعايير التصميمية المطلوبة, وكانت متوسطة في محطتين فلم يحقق التدفق النهائي الناتج عنهما جميع المعايير التصميمية المطلوبة, وسيئة في محطة واحدة والتدفق النهائي الناتج عنها فلم يحقق أياً من المعايير التصميمية المطلوبة. لذا نوصي في هذا البحث بضرورة إجراء قياسات دورية في كل محطة لمؤشرات التلوث من أجل المراقبة والضبط لكفاءة منشآت المعالجة. In spite of the significant increase in the number of Wastewater treatment Plants implemented in Syria, but we are still suffering from many problems caused by the lack of efficiency in the operation of the current projects. This research aims to assess the treatment efficiency and the quality of the final effluent in accordance with the required design standards for four small wastewater treatment plants in Latakia city, all working in extended aeration technology. Laboratory analyzes and measurements periodically for eight months starting from the month of February and until the month of September of the year 2013 were conducted for the indicators: dissolved oxygen (DO), biochemical oxygen demand (BOD), total suspended solids (TSS), nitrate (NO3-), phosphate (PO4-3). The results showed that the efficiency of the treatment was good at only one plant and the final effluent achieved all the required design criteria, average in two plants and the final effluent did not achieve all the required design criteria, and bad at one plant and the final effluent did not achieve any of the required design criteria. In this research, we recommend to the need for periodic measurements at each plant for pollution indicators in order to monitor and adjust the efficiency of treatment facilities.